Water Splitting on Titanium Oxide nanomaterial: a theoretical investigation - Pandey, Lila Ballav (Annual Oxford Journal, 2025)
The step-by-step electrochemical mechanism of water splitting by removal of protons and electrons is examined for the reaction of one and two water molecules on a Ti2O4 cluster. Density functional theory (B3LYP) and coupled cluster single-point calculations are employed to compute gas-phase reaction energies. The Polarizable Continuum Model (PCM) is utilized to calculate energies in the aqueous phase. Both neutral and alkaline media are considered. Proton and electron removal steps are generally found to be highly endothermic, except for proton removal steps in alkaline medium. The effect of an external potential on reaction energies is considered. Oxygen-oxygen bonds form after the removal of only two electrons (or one electron for the one water case).